Broadening Participation: The Why and the How. - Eney, Crystal; Lazowska, Ed; Martin, Hélène; Reges, Stuart (Computer (00189162), 2013)
There are many reasons for striving to increase the representation of women in the computing field, but the most compelling one is the enhanced quality of the solutions diverse contributors can achieve. This is one of five articles providing industry perspectives on gender diversity in computing.